APPLICATION OF CHARACTER EDUCATION FOR BEKASI NATURAL SCHOOL - Dina Solehati (Fakultas Ekonomi Universitas Negeri Jakarta, 2018)
Education is an effort to humanize humans. Through human education it is expected to be able to distinguish between good and bad things. Character education is in the spotlight today. This is because of the many phenomena in society that show the moral decline of the generation of the nation. Character is character which is the roundness of the human soul which manifests in the unity of mind movement, feeling and will or will which then produces energy to always think, feel and always use size, scales and definite and fixed basics. Through education, it is hoped that human intelligences arise not only as intellectuals but also other intelligences. In the 2013 curriculum, character education is highly preferred. This is in line with the Law on the national education system, which implies three domains of educational goals that must be achieved. The three objectives of education are the development of national character and civilization as an existential goal, the intellectual life of the nation as a collective goal, and the development of potential students as individual goals.